Prophetic Ethics and Local Habitus: A Living Hadith Study on Farewell Rituals in Madurese Muslim Society - Moh. Amiril Mukminin; Raharjo Raharjo; Siti Mujibatun (Prodi Ilmu Hadis Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This study examines the process of contextualizing al-Sunnah al-Nabawiyah within the Nater Hajjiyân tradition among the people of Bangkalan, Madura. The tradition is not merely understood as a religious ritual but also as a social mechanism that embodies prophetic values in daily life. Employing a descriptive qualitative approach through the methods of living hadith and religious ethnography, this research explores how the values of the Prophet’s Sunnah such as kinship, generosity, trustworthiness, and prayers for safety are internalized within the community’s social practices. The findings reveal that Nater Hajjiyân serves as both a social and religious space that strengthens social cohesion, constructs participatory religious authority, and provides a concrete medium for the actualization of prophetic teachings within local culture. The figures of kyai (religious leaders) and blater (social influencers) play pivotal roles in maintaining the balance between spiritual and social authority, affirming that religious legitimacy is formed through social practice rather than normative texts alone. The tradition has also undergone transformation in the digital era, where its rituals and spiritual values are documented and disseminated through social media as expressions of collective religious identity. This study concludes that the Nater Hajjiyân tradition represents a dynamic form of living Sunnah, demonstrating that the Prophet’s teachings continuously adapt to the socio-cultural context of society. Hence, the contextualization of Sunnah is not merely an act of interpretation but also a process of actualizing prophetic values in modern social life.